First carbon isotope chemostratigraphy of the Ouled Abdoun phosphate Basin, Morocco; implications for dating and evolution of earliest African placental mammals - (:unkn) unknown (My University, 2014)
This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their personal website or institutional repository. Authors requiring further information regarding Elsevier's archiving and manuscript policies are encouraged to visit: http://www.elsevier.com/authorsrights The well-known Maastrichtian-Ypresian vertebrate-bearing phosphate series, in the Ouled Abdoun Basin, Morocco, is classically dated using regional selachian biostratigraphic zonation. These marine sediments yielded Paleocene and Eocene mammals comprising the earliest known placentals from Africa. This study provides the first insight into the organic carbon isotope chemostratigraphy (δ 13 C org) of the Moroccan phosphate series and a refined dating of its vertebrate-bearing levels. Four Paleocene-Eocene sections in the NE Ouled Abdoun quarries show consistent δ 13 C org long term evolutions, from the base to the top: 1) positive trend in phosphorite Bed IIa, beginning with the lower Bone Bed yielding mammals such as Eritherium, Ocepeia, Abdounodus, Lahimia, of early Thanetian and Selandian age; 2) transitional negative trend in the Intercalary phosphorite Beds II/I that includes the Otodus obliquus and Phosphatherium escuilliei Bone Bed of earliest Ypresian age; 3) negative trend to the lowermost δ 13 C org values that are correlative to the early-middle Ypresian interval including ETM 2 and ETM 3 hyperthermal events in the global record; 4) positive trend in chert-enriched facies containing the middle Ypresian EECO global climatic event. Our chemo
Keywords: African Research